2004
DOI: 10.1002/art.11422
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of synovial lining macrophages in the promotion of transforming growth factor β–mediated osteophyte formation

Abstract: Objective. To investigate in vivo and in vitro whether macrophages have an intermediate role in transforming growth factor ␤ (TGF␤)-induced osteophyte formation.Methods. In vivo, synovial lining macrophages were selectively depleted by injection of clodronateladen liposomes 7 days prior to injection of 20 ng or 200 ng of TGF␤ into murine knee joints 3 times, on alternate days. Total knee joint sections were obtained on day 7 after the last injection and stained with Safranin O. Production of bone morphogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
3
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(166 citation statements)
references
References 34 publications
6
155
3
2
Order By: Relevance
“…(47) In addition, depletion of macrophages in osteoarthritic models reduced osteophyte formation dramatically. (48) Interestingly, a recent publication reported that preventing the recruitment of inflammatory macrophages in a CCR2 À/À mouse nonunion fracture model resulted in reduced endochondral bone formation but did not impede intramembranous bone formation. (49) This study demonstrated that at least some of the macrophages involved in endochondral bone formation are a recruited cell population, but a remaining question is whether resident macrophages also play a role in endochondral bone formation during fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…(47) In addition, depletion of macrophages in osteoarthritic models reduced osteophyte formation dramatically. (48) Interestingly, a recent publication reported that preventing the recruitment of inflammatory macrophages in a CCR2 À/À mouse nonunion fracture model resulted in reduced endochondral bone formation but did not impede intramembranous bone formation. (49) This study demonstrated that at least some of the macrophages involved in endochondral bone formation are a recruited cell population, but a remaining question is whether resident macrophages also play a role in endochondral bone formation during fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…The collagenase injection causes weakening of ligaments leading to gradual onset of OA pathology within six weeks of induction, without any direct collagenase-induced cartilage damage being observed. If macrophage depletion had been achieved prior to the elicitation of experimental OA, there was potent reduction of both fibrosis and osteophyte formation (Blom et al, 2004(Blom et al, , 2007avan Lent et al, 2004). This would indicate that in this murine model of OA, synovial macrophages control the production of the growth factors that promote fibrosis and osteophyte formation, both key pathophysiological events in OA.…”
Section: Macrophages Drive Both Inflammatory and Destructive Responsementioning
confidence: 98%
“…It can be speculated that once the macrophages are removed, the synovial fibroblasts change their phenotype and downregulate their production of both proinflammatory cytokines and destructive MMPs. An important series of papers, using injections of liposome-encapsulated clodronate to induce depletion of synovial lining macrophages, has provided some intriguing new information about the role of macrophages in driving degenerative changes in a mouse model of experimental OA induced by injection of collagenase (Blom et al, 2004(Blom et al, , 2007a. The collagenase injection causes weakening of ligaments leading to gradual onset of OA pathology within six weeks of induction, without any direct collagenase-induced cartilage damage being observed.…”
Section: Macrophages Drive Both Inflammatory and Destructive Responsementioning
confidence: 99%
“…Complementary DNA was used for each real-time PCR reaction (ABI Prism 7300 system; Applied BioSystems, Foster City, CA) in an RT 2 Profiler PCR Array human osteogenesis system (APHS-026A; SuperArray, Frederick, MD) with RT 2 RealTime SYBR Green PCR master mix (PA-012; SuperArray) according to the manufacturer's instructions. Collected data were interpreted using the ⌬⌬C t method.…”
Section: Rna Extraction and Reverse Transcription-polymerase Chain Rementioning
confidence: 99%